2006
DOI: 10.1897/04-560r.1
|View full text |Cite
|
Sign up to set email alerts
|

How terrestrial snails can be used in risk assessment of soils

Abstract: Among soil invertebrates, terrestrial snails are herbivorous and detritivorous organisms exposed to polluted soils by both digestive and cutaneous routes. Using laboratory-reared snails (Helix aspersa aspersa), we describe how the effects of contaminants on survival and growth of snails can be evaluated in laboratory bioassays. A national ring test was performed to assess the effect of Cd added to the soil or to the food. The ecotoxicity of sewage sludge also was evaluated. The present results demonstrate that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 79 publications
(46 citation statements)
references
References 41 publications
2
43
0
1
Order By: Relevance
“…Besides these two HM pairs, there were also significant correlations between the whole body Pb and Zn concentrations (r = 0.59-0.65, p < 0.001) as well as between Cu-Zn and Pb-Zn pairs for the whole body without hepatopancreas (r = 0.20-0.73, 0.05 < p < 0.001) [21]. In addition to the exposure to HMs via food uptake, land snails regularly eat soil and they are also exposed to HMs via epithelial contact [40]. As a result, future studies should be designed to verify our hypothesis and to elucidate such complex interactions between HMs during their transfer in the biota.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides these two HM pairs, there were also significant correlations between the whole body Pb and Zn concentrations (r = 0.59-0.65, p < 0.001) as well as between Cu-Zn and Pb-Zn pairs for the whole body without hepatopancreas (r = 0.20-0.73, 0.05 < p < 0.001) [21]. In addition to the exposure to HMs via food uptake, land snails regularly eat soil and they are also exposed to HMs via epithelial contact [40]. As a result, future studies should be designed to verify our hypothesis and to elucidate such complex interactions between HMs during their transfer in the biota.…”
Section: Resultsmentioning
confidence: 99%
“…Terrestrial gastropods regularly eat soil [40], and therefore, they accumulate heavy metals not only via food from the food chain, but also via contaminated soil. Because Helix pomatia spends its entire life on or in the upper soil horizons, for each location the soil samples were collected (25 g/sample in triplicate) from the top 15 cm layer after removal of vegetation (grass).…”
Section: Discussionmentioning
confidence: 99%
“…However, all these examples concern the aquatic environment because terrestrial bioassays with soil invertebrates are rare: we found only one experiment on a pest slug, reporting the high sensitivity of the embryos to metal salts [51]. Methods on this part of the life cycle would complete existing bioassays for the assessment of chemicals on snail survival, growth and reproduction [2,11,52] and, more generally, terrestrial bioassays used for risk assessment, such as tests on nematodes [5], earthworms [53], honeybee larvae [54,55] or birds [56].…”
Section: Utility and Limits Of An Embryotoxicity Bioassay With Snail mentioning
confidence: 99%
“…Copse snails (Arianta arbostorum) are known to be both herbivorous and detritivorous organisms that can be exposed to contaminated soils by both digestive and cutaneous routes. Snails are also regarded as key components of terrestrial food webs, and they may contribute to the transfer of pollutants from soil and plants to top predators (de Vaufleury et al, 2006). Earthworms are commonly tested in bioaccumulation studies, because they have a high exposure potential to chemicals in soil, and are important part of diet to a variety of wildlife species (DeForest et al, 2011).…”
Section: Introductionmentioning
confidence: 99%